Marketing of processed aren agroindustry (kolang–kaling) rokan hulu district - Sispa Pebrian; Evy Maharani; El Syabrina; Angga Pramana (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
The purpose of this study was to look at the marketing of processed sugar palm agroindustry (Kolang – Kaling) in Rokan Hulu Regency. This research was carried out by Rokan Hulu Regency because Rokan Hulu Regency is one of the regencies that has a large distribution of palm plants and has developed in the household industry. This research was carried out using a survey method on consumers who consume palm agro-industrial products, namely kolang-kaling. Respondent collection was carried out using the Simple Random Sampling method. The survey was conducted purposively which aimed to find out how the marketing process of kolang-kaling products occurred in Rokan Hulu Regency. The results show the response of consumers to the appearance of the product, packaging that still does not use special packaging, and the absence of product labels. Meanwhile, in terms of price, kolang-kaling follows the prevailing price in the market, which is Rp. 10,000 – 15,000. The distribution of kolang-kaling is carried out to traditional markets only, and promotional activities are still carried out on a limited basis (direct sales).